2016
DOI: 10.3389/fmicb.2016.00049
|View full text |Cite
|
Sign up to set email alerts
|

Reservoirs of Non-baumannii Acinetobacter Species

Abstract: Acinetobacter spp. are ubiquitous gram negative and non-fermenting coccobacilli that have the ability to occupy several ecological niches including environment, animals and human. Among the different species, Acinetobacter baumannii has evolved as global pathogen causing wide range of infection. Since the implementation of molecular techniques, the habitat and the role of non-baumannii Acinetobacter in human infection have been elucidated. In addition, several new species have been described. In the present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
130
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 94 publications
(103 reference statements)
2
130
0
2
Order By: Relevance
“…In traditional PH remediation processes, a single microorganism is generally applied to remove PH from the pollution area . However, it has been reported that single microorganisms prefer one or several types of PH, which makes it difficult to remove all types of PH contamination .…”
Section: Introductionmentioning
confidence: 99%
“…In traditional PH remediation processes, a single microorganism is generally applied to remove PH from the pollution area . However, it has been reported that single microorganisms prefer one or several types of PH, which makes it difficult to remove all types of PH contamination .…”
Section: Introductionmentioning
confidence: 99%
“…are found in wet environments, including moist soil/mud, wetlands, ponds, water treatment plants, fish farms, wastewater, and even seawater (3). These environmental strains often harbor antibiotic resistance mechanisms, including carbapenemases and extended-spectrum ␤-lactamases (ESBLs) (3), and may thus serve as important environmental reservoirs for resistance elements that transform into clinically relevant strains. Some medically relevant species, such as A. calcoaceticus, A. lwoffii, A. nosocomialis, and A. pittii, have been found on vegetables, meat, dairy products, and human skin (16).…”
mentioning
confidence: 99%
“…Such strains have harbored extensive antibiotic resistance repertoires. Furthermore, A. baumannii strains harboring extensive antibiotic resistance have contaminated commercial food, including meat, vegetables, and various types of livestock, suggesting multiple environmental routes of transmission into human populations (3,(17)(18)(19). However, non-baumannii Acinetobacter spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acinetobacter, implicated in recurrent aphthous stomatitis, periodontitis, nosocomial, and opportunistic infections particularly in tropical regions including India and Haemophilus, another genus linked to dysbiosis and invasive infections were more abundant in Indians' saliva (AlAtrouni et al, 2016;Chu et al, 1999;Patil & Chopade, 2001;Souto, Silva-Boghossian & Colombo, 2014;Kim et al, 2016;Said et al, 2014). The relevance of oral reservoirs of potential medical pathogens relevance merits further study.…”
mentioning
confidence: 99%